OBSTACLES TO MANAGING MSMES PRODUCT TRADEMARKS AT THE AL-FATIMAH ISLAMIC BOARDING SCHOOL, BOJONEGORO - Putri, Nabila Devinta Salsa Apriliant; Armeilia, Revina; Marzuqi, Muhammad Ilyas (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2023)
The Al-Fatimah Modern Islamic Boarding School Foundation is one of the institutions with the highest number of students in Bojonegoro Regency, East Java. This situation has prompted the foundation to produce hygiene products such as laundry detergent, bathing soap, laundry perfume, and dishwashing soap. Due to a lack of branding, these products are currently limited to internal consumption within the boarding school and cannot be sold in the market. This article describes the challenges faced by micro, small, and medium-sized enterprises (MSMEs) at the Al-Fatimah Islamic Boarding School in obtaining a trademark. Additionally, it will describe efforts to develop MSME products to make them known to the market. This research utilises a qualitative descriptive method, with informants including the production team leader, marketing personnel, and MSME product users at the Al-Fatimah Islamic Boarding School in Bojonegoro Regency. Data collection is carried out through in-depth interviews and participatory observation. Descriptive data analysis techniques are employed in this study. The research findings reveal that the main obstacle in obtaining a trademark for MSME products at Al Fatimah is a need for more understanding of the trademark application procedures.